Role of Notary in Registration Electronic Fiduciary (Study at Notary Office Weny Masitawati S.H , M.Kn) - Pulung Sedono, Hafidh (International Significance of Notary, 2023)
Abstract : The registration of fiduciary guarantee changed from a manual system to an online system. It is stipulated in Government Regulation No. 21 year 2015 About Fiduciary Guarantee Registration Procedures and Creation of Deed MakingFiduciary Guarantee Fees. But there are weaknesses in the implementation of its registration. The weakness contained in Article 4 that the regulation of fiduciary guarantee for registration period are 30 days after the deed was signed, but it did not give the arrangements for fiduciary guarantee which have not been registered after the government regulations was applicable. This study aims to investigate the implementation of fiduciary guarantee registration by government regulation and find out a solution to the shortcomings of the regulation. This research is an empirical jurisdiction with descriptive analytical approach, whereas the data obtained from primary data through interview the speakers, while secondary data obtained from the legislation and the literature. The Government Regulation No. 21 year 2015 About Fiduciary Guarantee Registration Procedures and Creation of Deed MakingFiduciary Guarantee Fees is an arrangement falsifies of fiduciary guarantee registration system from a manual system to an online system. That government regulation settingthe time of fiduciary guarantee period with online registration, the fiduciary guarantee who have not registered online after the government regulations was applicable, the fiduciary guarantee will fall by itself, so it must be made the a fiduciary guarantee and registered immediately with online systemat the notaryoffice. Keywords : Registration, Fiduciary, Notary, Online System